2D Electron System with Quasiparticle Auxiliary Field Correlation of Open quantum System - Das, Santosh Kumar; Dhobi, Saddam Husain; Nakarmi, Jeevan Jyoti (Patan Prospective Journal, 2022)
The objective of this work is to develop the mathematical model for the auxiliary field and interlink the pair correlation in the external potential of the open quantum system of the 2D electron system. For this, we used 2D Hubbard Model with the action open quantum system Lindblad equation and then apply the saddle point condition to obtain the auxiliary field of the 2D system. The obtained pair correlation of quasiparticles was found symmetric in nature with cooper pairs electron paring angle. The pair correlation of 0K was found 0.1times, 1 time, 2 times, 3 times, 4 times, and 5 times greater when compared with 0.2K, 0.3K, 0.4K, 0.5K, and 0.6K, respectively at -1 radian and +1 radian copper pairs electron pairing angle which is maximum. In addition, with increasing the temperature, the pair correlation decrease and become minimum without loss of symmetry.